Bioactivity and toxicity of coumarins from African medicinal plants - Anywar, Godwin; Muhumuza, Emmanuel (Frontiers in Pharmacology, 2024)
Introduction: Coumarins are naturally metabolites from plants and and a few micro-organisms. They have been widely used in the food, drug, and industry in their natural or synthetic forms. Numerous coumarins possess several biological activities such as anti-inflammatory, anti-ulcers, anti-tumour, anti-microbial, anti-coagulant. The aim of this study was to assess the bioactivity, and toxicity of coumarins from African medicinal plants. Methods: We searched online databases and search engines such as PubMed, Google Scholar and Web of Science for key terms such as coumarins, toxicity, bioavailability, bioactivity with appropriate Boolean operators. Only fulllength research articles published in English between 1995 to 2023 were reviewed. Results: We recorded 22 coumarins from 15 plant species from Africa. Most of the plant species (33%) were from North Africa. These were followed by East Africa at 21%, then West, and Central Africa at 18.2% each. Most of the coumarins (21.3%) were isolated from the entire plant and the leaves (19.1%) and most of them (46.7% or 10/24) had some antimicrobial activity. Five coumarins viz osthole, pseudocordatolide C & calanolide, chartreusin and esculetin had either antitumor or anticancer activity. Six coumarins had varying levels and types of toxicity ranging from inhibiting blood clotting as anticoagulants, to cytotoxic effects, causing hyperventilation, tremor, & photophobia, pulmonary hemorrhage, carcinogenic activity, severe neurotoxicity, hepato-and phototoxicity. Conclusion: Several African medicinal plants are sources of various coumarins that possess several biological activities as well as toxicities. This calls for more research into their safety and efficacy because of their wide spread applications as therapeutic agents.